Exploring the Role of Conversational Cues in Guided Task Support with Virtual Assistants - Vtyurina, Alexandra; Fourney, Adam (2018 ACM Conference on Human Factors in Computing Systems (CHI), 2018)
Voice-based conversational assistants are growing in popularity on ubiquitous mobile and stationary devices. Cortana, as well as Google Home, Amazon Echo, and others, can provide support for various tasks from managing reminders to booking a hotel. However, with few exceptions, user input is limited to explicit queries or commands. In this work, we explore the role of implicit conversational cues in guided task completion scenarios. In a Wizard of Oz study, we found that, for the task of cooking a recipe, nearly one-quarter of all user-assistant exchanges were initiated from implicit conversational cues rather than from plain questions. Given that these implicit cues occur in such high frequency, we conclude by presenting a set of design implications for the design of guided task experiences in contemporary conversational assistants.